Preventing sexual harm: positive criminology and sexual abuse - Kewley, Stephanie (Routledge studies in crime and society, 2021)
Introduction -- Definition, causes, and prevalence of sexual abuse -- Current approaches to sentencing and management -- Current approaches to the assessment of sexual offending -- Current approaches to the treatment of sexual offending -- Prevention strategies of sexual harm -- Positive criminology as an alternative -- Current positive criminology applications in terms of assessment -- Current positive criminology applications in terms of treatment and management.